Analysis of combined action of seismic loads and alkali-silica reaction in concrete dams considering the key chemical-physical-mechanical factors and fluid-structure interaction. (15th September 2019) - Pourbehi, Mohammad S.; van Zijl, Gideon P.A.G.; Strasheim, J.A.vB.
Highlights: The modelled and observed responses of the Fontana dam are in good agreement. The seismic responses of ASR affected and non-affected concrete dams differ. ASR induced cracking and material degradation change dam vibration characteristics. Abstract: This paper presents the results of the numerical analysis of concrete dam structures which are affected by Alkali Silica Reaction (ASR) and subjected to seismic load. In this research a Chemo-Thermo-Mechanical ASR Finite Element numerical code is developed to model and analyse this phenomenon in concrete dams. It considers the effects of variables such as temperature, non-uniform time-dependent material degradation and 3D stress confinement on ASR evolution. The model is validated by modelling the mechanical response of the Fontana gravity dam and comparing the results with the actual data on macro crack appearance and crest displacement. While the structural behaviour of ASR affected structures under monotonic and quasi-static loading has been extensively investigated over the last decades, limited research has addressed the effect of dynamic loads on structures affected by ASR. The combined effect of old and new cracks under dynamic excitation may cause dam failure. The numerical simulations are used to assess and predict the dynamic stability of the Koyna dam considering fluid-structure interaction and are also used to investigate the evolution of damage associated with inception and development of macro cracks in the dam structure due to the combined effect of the synthetic ASR and realistic seismic loading on the dam. The results show that this combined action can significantly change the dynamic behaviour of typical concrete dams due to concrete material degradation and crack development.